Soft figs shelf life increasing with and 1-methylcyclopropene and cold storage - de Jesus, Gabriel Lucas; Scheffer de Andrade Silva, Ricardo; Brasil Dias Tofanelli, Mauro; Lorena Cuquel, Francine (Revista Ceres, 2022)
The best sensorial Brown Turkey figs for the fresh market are the ones harvested soft. However, at this maturity stage, they have a very short shelf life, from two to seven days, depending on environmental conditions, which make their marketing very difficult. This research’s goal was to increase the shelf life of soft ‘Roxo de Valinhos’ figs, a ‘Brown Turkey’ plant material grown in Brazil, stored under refrigeration, by applying 1-methylcyclopropene (1- MCP), an ethylene inhibitor. Soft ‘Roxo de Valinhos’ figs were submitted to 1-MCP at 0; 0.5; 1.0 and 1.5 µg. L-1 for 24 h in airtight, under refrigeration at 4 ± 1 ºC. Subsequently, fruits were stored for up to 17 days at 4 ± 1 ºC. After removing from refrigerated conditions, fruits were kept for one day at room temperature (22 ºC), and then they were evaluated to determine their physical and chemical features. 1-MCP at 1.5 µg. L-1 was able to increase the soft figs shelf life to 12 days.